2022
DOI: 10.3390/f13091476
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Climate Change and Pro-Environmental Behavioral Intentions of Forest Recreation Area Users—A Case of Taiwan

Abstract: This study aims to extend the theory of planned behavior to explore climate change perception, adaptation intention, and behavioral patterns of PEB of tourists in the Xitou Nature Education Area (XNEA) in Taiwan. Furthermore, we analyzed the correlation among various variables using partial least squares structural equation modeling (PLS-SEM). Data were collected from the close-ended question questionnaires; sample size (n = 626). SPSS 22.0 and AMOS 22.0 for Windows were used as tools for analysis. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…PEB were moderately influenced by behavioral intention with 30% of the variances explained by this model. Chang et al [9] applied the theory of planned behavior to understand the PEB of tourists visiting a nature education area in Nantou, Taiwan. 84% of the variances of PEB were explained by the model with attitude having the strongest influence, followed by subjective norms and perceived behavioral control.…”
Section: Pro-environmental Behaviors Of Taiwanesementioning
confidence: 99%
See 2 more Smart Citations
“…PEB were moderately influenced by behavioral intention with 30% of the variances explained by this model. Chang et al [9] applied the theory of planned behavior to understand the PEB of tourists visiting a nature education area in Nantou, Taiwan. 84% of the variances of PEB were explained by the model with attitude having the strongest influence, followed by subjective norms and perceived behavioral control.…”
Section: Pro-environmental Behaviors Of Taiwanesementioning
confidence: 99%
“…From the various works regarding the PEB of Taiwanese, the theory of planned behaviors was widely used. The surveyed respondents were mostly specified targeted group of people by geographical location [4,10] or specified roles [7][8][9], with a wide range of accounted variances regarding PEB. In addition, subjective norms, the perceived social pressure to engage in a particular behavior, were noted by several researchers to significantly influenced PEB intentions [6,10].…”
Section: Pro-environmental Behaviors Of Taiwanesementioning
confidence: 99%
See 1 more Smart Citation
“…PEB has been described by Rezapouraghdam et al (2018) as engaging in activities that promote sustainable practices by reducing or eliminating negative environmental impacts (see also Javeed et al, 2022). Thus, as Mackay and Schmitt (2019) and Chang et al (2022) point out, it is important to understand what influences people's attitudes toward climate change and their PEB.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Spence et al (2011) found that experiencing disasters caused by climate change leads to increased concern and willingness to reduce energy consumption (see also Davidson & Kecinski, 2022). As described by Tierney (2019) and Chang et al (2022), previous disaster experiences, as well as the perception of being part of a collective, lead to the use of a larger repertoire of adaptation strategies, which includes PEB.…”
Section: Introductionmentioning
confidence: 99%